Enhanced Antimicrobial and Biofilm-Disrupting Properties of Gallium-Doped Carbon Dots - Radha, Remya (2025)
Antibiotic resistance continues to be a global health threat caused by microbial biofilms, yet carbon dots (CDs) offer a promising countermeasure. Doping CDs with metals or nonmetals further enhances their properties while maintaining biocompatibility. This work reports the sonochemical synthesis of gallium–boronic acid carbon dots (Ga-BACDs) under conditions (20 kHz, 2000 W, 60% amplitude, 60 °C, and 60 min), achieving significant gallium incorporation. Ultraviolet–visible and fluorescence analyses reveal characteristic CD absorbance peaks at 286 and 355 nm and strong emission at 397–400 nm. Fourier transform infrared spectral changes on Ga-BACDs suggest successful incorporation of gallium and confirm Ga–H/Ga–O–C (2000–2600 cm⁻¹) and Ga–O/Ga–O–Ga (400–700 cm⁻¹) vibrations. X-ray diffraction and Raman spectroscopy data indicate the retention of the amorphous carbon framework with enhanced local ordering. High-resolution scanning electron microscopy (HR-SEM) and high-resolution transmission electron microscopy images demonstrate morphological alterations compared to BACDs with a particle mean diameter of 8.6 ± 4.1 nm. The gallium doping in Ga-BACDs was quantified as 3.66 ppm by using inductively coupled plasma–atomic emission spectroscopy. X-ray photoelectron spectroscopy results indicated that Ga is chemically integrated inside the carbon dot framework. The zeta potential shifts from −32.5 mV (BACDs) to −23.3 mV (Ga-BACDs), evidencing surface charge modulation. The antimicrobial activity of Ga-BACDs was tested against Gram-positive (Staphylococcus epidermidis) and Gram-negative (Escherichia coli) bacterial strains; the presence of gallium contributed to improved bioactivity at 37 °C. HR-SEM images of Ga-BACD-treated bacteria presented significant structural damage, membrane rupture, and surface irregularities. Ga-BACDs inhibited biofilm formation at concentrations as low as 2.5 mg/mL and efficiently eradicated preformed biofilms, highlighting their promise for preventing biofilm-associated infections. MTT assays on normal human brain cells confirm the biocompatibility of Ga-BACD-coated cellulose discs and CD solution (0.1 mg/mL), supporting the safe use of Ga-BACD-modified fibers. Overall, our findings highlight Ga-BACDs as metal-doped carbon nanoparticles, with strong potential for novel antibacterial treatments.